Numerical study of molten and semi-molten ceramic impingement by using coupled Eulerian and Lagrangian method. (15th May 2015) - Zhu, Zihang; Kamnis, Spyros; Gu, Sai
Abstract: Large temperature gradients are present within ceramic powder particles during plasma spray deposition due to their low thermal conductivity. The particles often impinge at the substrate in a semi-molten form which in turn substantially affects the final characteristics of the coating being formed. This study is dedicated to a novel modeling approach of a coupled Eulerian and Lagrangian (CEL) method for both fully molten and semi-molten droplet impingement processes. The simulation provides an insight to the deformation mechanism of the solid core YSZ and illustrates the freezing-induced break-up and spreading at the splat periphery. A 30 μm fully molten YSZ particle and an 80 μm semi-molten YSZ particle with different core sizes and initial velocity ranging from 100 to 240 m/s were examined. The flattened degree for both cases were obtained and compared with experimental and analytical data.